Pharmaceutical Patents and Prices : A Preliminary Empirical Assessment Using Data from India - Duggan, Mark; Goyal, Aparajita (World Bank, Washington, DC, 2012)
The enforcement of stringent intellectual property rights in the pharmaceutical sector of developing countries generates considerable controversy, due to both the extensive research investment and the public policy importance of this sector. This paper explores the likely effects of enforcing product patents on prices and utilization of drugs in the Central Nervous System market in India. The Central Nervous System segment is the second largest therapeutic category in terms of retail sales in the world and is one of the fastest growing segments in India. Using information on product patents granted by the government and panel data on pharmaceutical prices and utilization from 2003-2008, the paper finds limited evidence of overall price increase following the introduction of product patents. However, there appear to be heterogeneous effects on prices by the type of product patent granted on drugs, implying the need for a careful examination of the product patent portfolio.